Eye movement desensitization and reprocessing (EMDR) facilitating rational emotive behaviour therapy (REBT) in the treatment of test anxiety - Ten Cate, Hein (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 1998.